DETEKSI KECURANGAN (FRAUD) DI SEKTOR PEMERINTAH - Taufik Kurrohman; Ekaning Pratiwi; Andriana Andriana (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2017)
This study aims to explore the perceptions of employees in government agencies regarding the effect of the effectiveness of internal control systems, compensation satisfaction, organizational culture, unethical behavior, leadership style, and law enforcement against fraud in the government sector. This study included a quantitive research with survey method. The data used is primary data collected through questionaires. The research sample of 223 employees a number of government agencies in Jember. The resu lts of this study indicate that there is a negative influence between the effectiveness of the internal control system to fraud in government sector, there is a negative effect between satisfaction and compensation to fraud in the government sector, there are no negative effects between the culture of the organization to fraud in the government sector, there are positive influence between behavior ethical against fraud in the government sector, there is a negative influence of leadership style to fraud in the government sector,there are no negative effects of enforcement against fraud in the government sector. Keywords: Perceptions of Employees, Fraud, Government Sector